Patients' experiences of physical activity on prescription with access to counsellors in routine care: a qualitative study in Sweden - Pia Andersen; Lena Lendahls; Sara Holmberg; Per Nilsen (BMC, 2019)
Abstract Background Physical activity on prescription (PAP) has been implemented in several countries, including Sweden, to support patients who might benefit from increased physical activity. This study explores the experiences of recipients of PAP in routine health care in Sweden that offers the recipients support from physical activity counsellors. The aim was to explore influences on engagement in physical activity by PAP recipients' from a long-term perspective. Methods We conducted individual semi-structured interviews using a topic guide with a purposively selected sample of 13 adult PAP recipients 1.5 to 2.5 years after PAP. Interviews were recorded, transcribed verbatim and analysed through inductive and deductive content analysis. The questions were informed by Capability-Opportunity-Motivation-Behaviour (COM-B), which was also used as a framework to analyse the data by means of categorizing the factors (influences on the behaviour). Results Ten factors (i.e. sub-categories) that influenced the participants' engagement in physical activity were identified. PAP recipients' capability to engage in physical activity was associated with adapting the PAP to the individual's physical capacity and taking into account the individual's previous experiences of physical activity. PAP recipients' opportunity to engage in physical activity was related to receiving a prescription, receiving professional counselling and follow-up from a physical activity counsellor, collaboration between prescriber and counsellor, having access to appropriate activities, having a balanced life situation and having support from someone who encouraged continued physical activity. PAP recipients' motivation to engage in physical activity was associated with the desire to improve his or her health condition and finding activities that encouraged continuation. Conclusions PAP recipients' engagement in physical activity was influenced by their capability, opportunity and motivation to undertake this behaviour. Numerous extraneous factors influence capability and motivation. Physical activity counsellors were found to be important for sustained activity because they use an individual approach to counselling and flexible follow-up adapted to each individual's need of support.